2017
DOI: 10.1055/s-0037-1608633
|View full text |Cite
|
Sign up to set email alerts
|

Angle of Progression on Ultrasound in the Second Stage of Labor and Spontaneous Vaginal Delivery

Abstract: The AoP has the potential to predict spontaneous vaginal delivery and the duration of the second stage of labor which may be useful in counseling patients and managing their labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The fetal head in both models started at an angle of progression of 1008, but at the moment of fetal head crowningdefined here as the point of maximum perineal body strain, as in previous studies-the Included Model had a larger value [20,21,25]. The superficial perineal structures increased the final fetal head angle of progression, indicating that the soft tissues in the Included Model were pushed further to reach an analogous moment of fetal head crowning.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The fetal head in both models started at an angle of progression of 1008, but at the moment of fetal head crowningdefined here as the point of maximum perineal body strain, as in previous studies-the Included Model had a larger value [20,21,25]. The superficial perineal structures increased the final fetal head angle of progression, indicating that the soft tissues in the Included Model were pushed further to reach an analogous moment of fetal head crowning.…”
Section: Discussionsupporting
confidence: 64%
“…Angle of progression is a twodimensional angle between the midsagittal, long (or semi-major) axis of the ellipse-shaped pubic symphysis and a line connecting royalsocietypublishing.org/journal/rsfs Interface Focus 9: 20190011 the inferior end of this axis to the vertex of the fetal skull measured at approximately the midsagittal plane [20,21]. This has been shown to be a more reliable, robust method for measuring fetal head progression during vaginal delivery and easier to define within a finite-element model than fetal head stations [20,21]. In this study, the concept of the angle of progression was also applied to the perineal body, where the first line is still the long axis of the pubic symphysis but the second extends to the centroid of the perineal body instead of the fetal head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural log of time to normal spontaneous delivery in the subgroup of primiparous women shows the highest association with HPD and AOP during uterine contraction (r = 0.742), making delivery time prediction comparable to utilising cervical dilatation. The AoP detected by transperineal ultrasound at the start of the second stage, according to Rouse et al (2017) [20] , may be able to predict the delivery method. A narrow AoP <153 degrees at complete cervical dilatation increased the likelihood of a prolonged second stage of labour and the need for a surgical delivery in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of Kameyama et al (30), trans-perineal ultrasonography examination shortly after complete cervical dilation was a useful predictor for predicting birth type. Bibbo et al (31) looked at the link between the angle of advancement determined by trans-peritoneal ultrasonography, the route of delivery, and the duration of the 2 nd stage in 137 patients. This study revealed that a progression angle of fewer than 153 degrees is linked to a higher risk of a prolonged pregnancy culminating in cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%